Durabilitas Mortar Geopolimer Di Air Gambut - Chrisfela Wulandari; Monita Olivia; Iskandar Romey Sitompul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This research studies the durability of OPC mortar, geopolymer mortar based fly ash and geopolymer mortar based palm oil fuel ash in acidic environment like peat water and netral environment like aquadest. This mortars will testing by mechanics and physical behaviour likes visual inspection and compressive strength after submerged in that water at age 7, 28, 91 and 120 days. The range of pH by peat water are 4,0-4,5. Geopolymer mortar based fly ash and geopolymer mortar based palm oil fuel ash use modulus activator (Ms)= SiO2/Na2O= 1 and %Na2O = 19%. This research show that the compressive strength of geopolymer mortar based fly ash (FA) increase in peat water and aquadest immersion, whereas the compressive strength of geopolymer mortar based palm oil fuel ash (POFA) decrease because the two type of this water immersion. The compressive strength of OPC mortar increase in aquadest immersion, but decrease in peat water immersion. Visual inspection of OPC mortar and geopoymer mortar based POFA changes become brown colored in peat water immersion.Keywords: durability, OPC, fly ash, palm oil fuel ash, geopolymer, peat water, aquadest, compressive strength, pH, alkali activator, and acidic environment